KUALITAS PELAYANAN WAITERS DI GRAND ZURI HOTEL DUMAI - Deswanti, Sinta; Sidiq, Siti Sofro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Hospitality is one of the important components that can support the development of the world of tourism. The Hospitality Industry is one of the industries that play an important role in the economic development and the world of tourism in Indonesia. service is any action or desire which may be offered by one party to another, essentially intangible and does not result in any ownership. And a sense of fun given to others who accompanied hospitality and ease in meeting the needs of consumers. This research was conducted in Grand Zuri Kota Dumai.Jl Jend. Sudirman No. 88, Dumai City, Bintan Village, Dumai City District, Dumai City. This hotel is chosen as a place of research because in it has the quality of service that visitors need when visiting this hotel. This study aims to determine the response of visitors to the quality of service at the Grand Hotel Zuri Dumai City. This research uses quantitative descriptive method to process the data obtained in the field through interviews, all the information collected and studied to become a unified whole (Kusuma and Sugono 2000). As for the sample in research sebanyan 100 respondents, data collection techniques used are observations, interviews, questionnaires, using Likert scale as a measuring tool. Based on the results of research that has been done quality service with variable Reliability, Responsivensse, Assurance Empathy and Tangible with good research conclusions.Keywords :Realibility, Responsivinsse, Assurance, Empathy, Tangible, Hotel Grand Zur